Membangun Literasi Anak Marginal Melalui Perpustakaan Literasi Nagari Sungai Nyalo - Siti Fatimah; Agustina Agustina; Zafri Zafri; Hera Hastuti; Wulandari Dwianty (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The Mandeh area is currently one of the tourist destinations that has beautiful scenery and its own uniqueness for tourists both from within and outside the country. The Mandeh area, which has these unique qualities, if not preserved and managed properly, will become extinct in the future. In order to promote tourism in the Mandeh area, especially the Nagari Sungai Nyalo, the service team carried out service activities in Nagari Sungai Nyalo as a Literacy Village to create sustainable tourism. So far, the children of Sungai Nyalo are classified as marginalized children. The purpose of this activity is to (1) provide literacy education to children in the Nyalo River village, (2) make the Nyalo River village as one of the areas in the Mandeh area into a sustainable tourism area. The method used in this activity is the social intervention method, which can be interpreted as a way or strategy in providing assistance to the community (individuals, groups, communities) to improve one's welfare through efforts to re-enable social functions. The results of this activity are (1) increasing children's interest in reading and literacy, (2) increasing children's confidence to be able to guide tourists visiting their villages.